2000
DOI: 10.1034/j.1600-051x.2000.027002109.x
|View full text |Cite
|
Sign up to set email alerts
|

The calcium channel blocker used with cyclosporin has an effect on gingival overgrowth

Abstract: The prevalence of gingival overgrowth in renal transplant recipients maintained on cyclosporin A and nifedipine is lower than those treated with cyclosporin A and amlodipine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 24 publications
2
39
1
2
Order By: Relevance
“…The differences in these investigations depend in part on culture conditions (James et al, 1998(James et al, , 2000. While cyclosporin A was found to increase glycosaminoglycan secretion by fibroblasts (Newell and Irwin, 1997), and nifedipine and phenytoin increased heparan levels (Saito et al, 1996), other studies failed to report any differences in vivo (Romanos et al, 1992(Romanos et al, , 1993Rocha et al, 2000;Martins et al, 2003).…”
Section: Direct Effects Of Phenytoin Cyclosporin and Nifedipine On mentioning
confidence: 92%
“…The differences in these investigations depend in part on culture conditions (James et al, 1998(James et al, , 2000. While cyclosporin A was found to increase glycosaminoglycan secretion by fibroblasts (Newell and Irwin, 1997), and nifedipine and phenytoin increased heparan levels (Saito et al, 1996), other studies failed to report any differences in vivo (Romanos et al, 1992(Romanos et al, , 1993Rocha et al, 2000;Martins et al, 2003).…”
Section: Direct Effects Of Phenytoin Cyclosporin and Nifedipine On mentioning
confidence: 92%
“…In 57.3%, cyclosporine A was administered in combination with calcium channel blockers. Higher prevalence of gingival hyperplasia was observed in the combina-binaciji ciklosporina A s amlodipinom, negoli u kombinaciji CSA s nifedipinom (28).…”
Section: Gašpar I Surmentioning
confidence: 97%
“…Naši rezultati pokazali su da je samo 48 posto naših pacijenata bilo kod tion of drugs cyclosporine A with amlodipine than in nifedipine with cyclosporine A (28).…”
Section: Gašpar I Surunclassified
“…Patients undergoing monotherapy with amlodipine had less gingival overgrowth than those taking nifedipine. 8 A cohort study of 135 renal-transplantation patients demonstrated that the combined use of cyclosporine and nifedipine caused less gingival overgrowth (53%) than that in patients treated with cyclosporine and amlodipine (72%). 8 Many studies showed that the combined use of CCBs and immunosuppressants enhanced the risk and severity of gingival overgrowth.…”
Section: Discussionmentioning
confidence: 98%